The Role of Caregiver on Pos PAUD’s Training Program to Improve Emergent Literacy Development Through Dialogic Reading Activity - Astuti, Tri Puji; Ekowarni, Endang (Indonesian Journal of Early Childhood Education Studies, 2014)
Research on emergent literacy states that young children learn about reading through experiences with oral language. The purpose of this study was to examine the effects of implementing dialogic reading techniques in a pos paud setting via caregiver training program by kader pos paud to improve emergent literacy development. In the first experiment, the sample consisted of 19 respondents in the control group and 17  in the experiment group. The result of the study indicated an improvement in emergent literacy knowledge and dialogic reading skill for kader pos paud that following the training program. The independent t-test result indicated that post-treatment score for the experiment group was significantly better than the control group. The paired t-test results showed significant gain between pre and post treatment for experiment group.The score was entered to SPSS version 17. In the second experiment, there are  8 children in the control group and 9 children in the experiment group.The emergent literacy test that made by the researcher  was used to determine the emergent literacy development of the subjects. The Mann Whitney test statistical method indicated significant gain between the experimental group and the control group. A Wilcoxon test revealed a significant gain in emergent literacy development for the experimental group. Therefore, this study found that a  caregiver  on  storybook  reading  may  lead  to  a  possible  positive  influenced    in  emergent  literacy development for the pre-kindergarten children whose caregivers attended the training program.How to citeAstuti, T., & Ekowarni, E. (2014). The Role of Caregiver on Pos PAUD’s Training Program to Improve Emergent Literacy Development Through Dialogic Reading Activity. Indonesian Journal Of Early Childhood Education Studies, 3(2), 84-93. doi:10.15294/ijeces.v3i2.9480